Comparative Effectiveness of Targeted Intrathecal Drug Delivery Using a Combination of Bupivacaine with Either Low-Dose Fentanyl or Hydromorphone in Chronic Back Pain Patients with Lumbar Postlaminectomy Syndrome. Issue 9 (11th May 2020) - Ade, Timothy; Roh, Justin; Sharma, Gautam; Mohan, Mahesh; DeLozier, Sarah J; Janes, Jessica L; Hayek, Salim M
Abstract: Objective: Targeted intrathecal drug delivery (TIDD) is an effective interventional pain management modality often used in postlaminectomy patients with refractory chronic low back pain. A combination of intrathecal bupivacaine with an opioid is often used. However, intrathecal catheter tip granulomas have occurred with use of morphine or hydromorphone but generally not with fentanyl. The objective of this study was to compare the efficacy of TIDD using bupivacaine/fentanyl vs bupivacaine/hydromorphone in patients with chronic intractable low back pain postlaminectomy. Materials and Methods: A retrospective comparative analysis of consecutive patients with lumbar postlaminectomy syndrome who were trialed and later received TIDD with a combination of bupivacaine/hydromorphone or bupivacaine/fentanyl between June 2009 and May 2016 at a single tertiary medical center. Results: We identified a cohort of 58 lumbar postlaminectomy patients receiving a TIDD admixture of either hydromorphone/bupivacaine (30 patients) or low-dose fentanyl/bupivacaine (28 patients) with at least two years of follow-up. The fentanyl group had significantly lower baseline opioid consumption and a lower rate of intrathecal opioid dose escalation. Both groups had similar and significant reductions in pain scores over the two-year follow-up period. No granulomas were observed. Conclusion: TIDD using a low-dose fentanyl admixture with bupivacaine in patients with postlaminectomy syndrome and refractory chronic low back pain results in similar pain relief to TIDD with hydromorphone and bupivacaine. Low-dose intrathecal fentanyl leads to a lower rate of opioid escalation and may be safer than hydromorphone.